2013
DOI: 10.1371/journal.pone.0069055
|View full text |Cite
|
Sign up to set email alerts
|

Noisy Galvanic Vestibular Stimulation Modulates the Amplitude of EEG Synchrony Patterns

Abstract: Noisy galvanic vestibular stimulation has been associated with numerous cognitive and behavioural effects, such as enhancement of visual memory in healthy individuals, improvement of visual deficits in stroke patients, as well as possibly improvement of motor function in Parkinson’s disease; yet, the mechanism of action is unclear. Since Parkinson’s and other neuropsychiatric diseases are characterized by maladaptive dynamics of brain rhythms, we investigated whether noisy galvanic vestibular stimulation was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 84 publications
(132 reference statements)
4
52
0
Order By: Relevance
“…The mechanism hypothesised to underlie this ameliorating effect is stochastic resonance, in which an optimal amount of noise added to a nonlinear system can enhance the information processing within this system, whereas a further increase in noise intensity degrades information transfer5678202122. An appropriate intensity of noise has been shown to intensify the detection of subthreshold signals in various sensory functions such as auditory perception, visual perception, and tactile sensations232425.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism hypothesised to underlie this ameliorating effect is stochastic resonance, in which an optimal amount of noise added to a nonlinear system can enhance the information processing within this system, whereas a further increase in noise intensity degrades information transfer5678202122. An appropriate intensity of noise has been shown to intensify the detection of subthreshold signals in various sensory functions such as auditory perception, visual perception, and tactile sensations232425.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of how SVS may influence the activity of the brain is not known, but may theoretically involve SR effects on thresholds in the activation pattern of basal ganglia output. SVS has been demonstrated to influence resting state electroencephalography activity indicating that cortical-subcortical activity is also modulated [12]. A recent rodent study demonstrated improved balance and locomotion in the rotarod test in 6-OHDA hemilesioned rats during near detection threshold SVS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wilkinson et al () have reported that GVS increased the amplitude of the N170 potential and the power of delta and theta EEG during a face processing task. A more recent study by Kim et al () also supports the idea that GVS modulates neural oscillations.…”
Section: Discussionmentioning
confidence: 61%